Covalent modification of Nanocellulose (NCC) by functionalized Graphene oxide (GO) and the study of adsorption mechanism. Issue 2 (1st February 2021) - Yu, Haibiao; Zhang, Shaobo; Wang, Yu; Yin, Dingwen; Huang, Jintian
ABSTRACT: In this study, nanocellulose/graphene oxide composites (NCC/GO) were prepared by dissolving NCC with AmimCl ionic liquid, and covalently modifying NCC with functionalized GO via esterification reaction, which weakened the hydrogen bonding of molecules and reduced chemical inertness. The morphology of modified NCC was characterized by SEM. The structure between NCC and GO was analyzed by FTIR. The crystalline phase of NCC and NCC/GO composites was investigated by XRD. The results revealed that NCC/GO composites were successfully prepared, and GO was uniformly dispersed in the NCC matrix. Because of the introduction of GO, it greatly increased the proportion of functional groups in composites. In addition, taking heavy metal ions-Ni 2+ as an example, the adsorption rate of NCC and NCC/GO composites on Ni 2+ was studied, and the adsorption mechanism also was explored. The experimental results showed that the adsorption rate of Ni 2+ by NCC/GO composites was 95.8% higher than that of pure NCC. Furthermore, the composites had multiple adsorption sites (–COOH, –OH, –C = O, pore structure) for heavy metal ions because of the grafting of GO onto NCC.–